2002
DOI: 10.1017/s1049023x00058878
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Devastating Effects of a Typhoon—A Prediction Model Based on Logistic Regression

Abstract: Result: There were 2,347 deaths and 11,305 persons were injured in this disaster. Based on the summary of deaths in the stricken areas, Taichung had highest number of deaths (1,777) followed by Nantou (824) and Taipei (132). The epicenter was located, within Nantou county whereas Taichung had the highest number of death. Total economic loss from this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As shown in Figure 6, it can be found that when the time step was set to 5 during the experiment, the AUC and Acc both achieved good results. The forecast results of the model were contrasted with three traditional machine learning algorithms used in classic tropical cyclone research, such as Logistic Regression (LR), Linear Discriminative Analysis (LDA), and Decision Tree (DT) [17][18][19] . In order to enhance the comparability, the model was also compared with the most primitive LSTM, which only considers the temporal relationship and does not consider spatial relationships.…”
Section: Fp Tnmentioning
confidence: 99%
“…As shown in Figure 6, it can be found that when the time step was set to 5 during the experiment, the AUC and Acc both achieved good results. The forecast results of the model were contrasted with three traditional machine learning algorithms used in classic tropical cyclone research, such as Logistic Regression (LR), Linear Discriminative Analysis (LDA), and Decision Tree (DT) [17][18][19] . In order to enhance the comparability, the model was also compared with the most primitive LSTM, which only considers the temporal relationship and does not consider spatial relationships.…”
Section: Fp Tnmentioning
confidence: 99%